Outcome of Mandibular Reconstruction Using Free Fibula Flap in Patients Treated at a Tertiary Care Center in Nepal - Pandit, Sudeep; Shrestha, Jayan Man; Lohani, Ishwar; Rayamajhi, Sangam; Sharma, Samit; Niraula, Himalaya; Rajbhandari, Bikesh; Thakur, Sadmarg; Yadav, Amit (Journal of Multidisciplinary Research Advancements, 2025)
Mandibular defects resulting from neoplasm, trauma, or infectious etiology are a major reconstructive challenge. Free fibula flap (FFF) is now considered the gold standard technique for restoring mandibular function and aesthetics with the development of microsurgery. However, in a developing country with a tertiary center, where resources are limited and patients often lack adequate financial and insurance support, the study’s outcomes are limited. A retrospective study was conducted on 11 patients who underwent mandibular reconstruction using the Free fibula flap (FFF) from 2021 to 2025. Variables included demographics, etiology, defect classification, flap outcome, postoperative complications, and oral feeding timeline. The data were collected from the medical records section and entered into Microsoft Excel 2019. The study was approved by the Institutional Review Committee (IRC) of the Institute of Medicine (IOM), Tribhuvan University. Out of 11 patients (7 men and 4 women), 6 had cancer-related issues, while 5 had non-cancerous conditions. One individual faced flap loss, resulting in a flap survival rate of 90.9%. Additionally, 6 patients encountered postoperative complications such as wound dehiscence, surgical site infections, and venous congestion. Those who did not experience complications were able to resume oral feeding within 2 weeks, whereas others required a longer recovery period. There was one case of donor site SSI. FFF-based mandibular reconstruction is feasible and effective even in resource-constrained settings. Despite limited access to advanced tools such as 3D planning and CT angiography, successful outcomes can still be achieved with skilled surgical teams and institutional support.